Teacher Competency Development Assistance in Improving The Quality of Learning in Elementary Madrasah - Haningsih, Sri; Hidayatulloh, Muhammad Syarif; Setiadi, Anggi Arif Fudin; Ardlina, Faizah Wahyu; Najma, Ma'rifah Nur (Kuras Institute & Scidac Plus, 2026)
Teacher competence plays a significant role in improving the quality of learning in primary education institutions, including Madrasah Ibtidaiyah. However, many teachers still face challenges in designing effective learning, implementing innovative teaching strategies, and conducting meaningful learning evaluations. This community service program aims to assist teachers in developing pedagogical competencies to improve the quality of learning in Madrasah Ibtidaiyah. The program employed a mentoring-based approach consisting of training, classroom mentoring, and reflective evaluation. The participants were teachers at a Madrasah Ibtidaiyah who were actively involved in the learning process. Data were collected through observation, interviews, and documentation of mentoring activities. The results indicate that the mentoring program improved teachers’ ability to design lesson plans, implement active learning strategies, and conduct learning assessments. In addition, the mentoring process increased teachers’ professional confidence and fostered collaborative learning. This program demonstrates that mentoring-based professional development can become an effective strategy for strengthening teacher competence and improving learning quality in Madrasah Ibtidaiyah.